Assessing differences in acoustic characteristics from impact and vibratory pile installation and their potential effects on the large yellow croaker (Pseudosciaena crocea) - Niu, Fuqiang; Xie, Jiarui; Zhang, Xuexin; Xue, Ruichao; Chen, Benqing; Liu, Zhenwen; Yang, Yanming (Frontiers in Marine Science, 2023)
Underwater noise from anthropogenic activities can cause negative behavioral and physical effects on marine life, including physical changes, injuries and death. Impact and vibratory pile driving are generally used for the construction of ocean-based foundations. Based on the filed data under a same marine engineering and marine environment, this paper addresses the characteristics and differences of underwater noise from impact and vibratory pile driving and the effects of noise on populations of large yellow croaker (Pseudosciaena Crocea). The impact pile driving pulse had a median peak-to-peak sound pressure source level (SPLpp) of 244.7 dB re 1μPa @ 1 m and a median sound exposure source level (SELss) of 208.1 dB re 1μPa2s @ 1 m by linear regression. The waveform of vibratory pile driving appears to be a continuous with a low SPLpp, but the cumulative SEL (SELcum) in 1min is very high, reaching 207.5 dB re 1μPa2s @ 1 m. The ranges of behavioral response for adult large yellow croaker (20-23 cm) are predicted to be 4798 m for impact pile driving and 1779 m for vibratory pile driving, respectively. The study provides evidence of the comparative potential effects of vibratory and impact pile driving on large yellow croaker, and reference for the conservation of croaker